Challenges to tackling antimicrobial resistance : economic and policy responses - Anderson, Michael; Cecchini, Michele; Mossialos, Elias (Cambridge : Cambridge University Press, 2019)
Antimicrobial resistance (AMR) is a biological mechanism whereby a micro-organism evolves over time to develop the ability to become resistant to antimicrobial therapies such as antibiotics. The drivers of and potential solutions to AMR are complex, often spanning multiple sectors. The internationally recognised response to AMR advocates for a'One Health' approach, which requires policies to be developed and implemented across human, animal, and environmental health. To date, misaligned economic incentives have slowed the development of novel antimicrobials and limited efforts to reduce antimicrobial usage. However, the research which underpins the variety of policy options to tackle AMR is rapidly evolving across multiple disciplines such as human medicine, veterinary medicine, agricultural sciences, epidemiology, economics, sociology and psychology. By bringing together in one place the latest evidence and analysing the different facets of the complex problem of tackling AMR, this book offers an accessible summary for policy-makers, academics and students on the big questions around AMR policy.
Title from publisher's bibliographic system (viewed on 06 Apr 2020).
Keywords: Drug resistance; Drug development